ANALYSIS OF THE NEED FOR SELF-ACTUALIZATION, AWARDS AND SOCIAL NEEDS TO ACHIEVEMENT EMPLOYEES IN. PT. KHARISMA PEMASARAN BERSAMA CABANG MEDAN - Fazhil Hanafi Asnora (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2018)
This study is based on the idea that the emergence of achievement is influenced by several factors driving, both of which come from outside the individual and of the individual. Power stimulus, impetus, the motivation that encourages employees to want to come to work diligently differ between employees with one another. This difference is caused by differences in motives, goals, and needs of each employee to work for the needs of employees of both material and non material should be filled in accordance with expectations when the expected high employee performance. This study aims to determine the effect simultaneously the needs of self-actualization, esteem, and social needs, to pertasi employees at PT. Kharisma Joint Marketing Branch Medan. The analysis technique used is multiple linear regression. The results showed that partially self-actualization needs (X1) positive and significant effect on employee performance (Y) with the value t count> t-table is 2,316> 2,037 with a significance value of 0.027> 0.05. Choice (X2) has no effect on employee performance (Y) with the value t count> t-table is 0.076 <2037 with a significance value of 0.940> 0.05. Social needs (X3) significantly positive effect on employee performance (Y) with the value t count> t-table is 2,237> 2,037 with a significance value of 0.022> 0.05. Variables simultaneously self-actualization needs (X1), awards (X2) and social needs (X3) simultaneously significant effect on employee performance (Y) at a rate of 95% or 5% alpha.